The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1038/gt.2008.9
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of a gene electrotransfer method for mesenchymal stem cell transfection

Abstract: Gene electrotransfer is an efficient and reproducible nonviral gene transfer technique useful for the nonpermanent expression of therapeutic transgenes. The present study established optimal conditions for the electrotransfer of reporter genes into mesenchymal stem cells (MSCs) isolated from rat bone marrow by their selective adherence to tissue-culture plasticware. The electrotransfer of the lacZ reporter gene was optimized by adjusting the pulse electric field intensity, electric pulse type, electropulsation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
52
1
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(57 citation statements)
references
References 56 publications
3
52
1
1
Order By: Relevance
“…It was recently reported that electroporation of cells in a capillary system gave rise to an enhancement of transfection rate and cell viability when compared to the cuvette system (Kim et al 2008). In the conventional electroporation, using a cuvette, the reported cellular viabilities are generally below 70 % and most importantly the cell recoveries are rarely mentioned, with the exception of few studies with primary cells (Aluigi et al 2006;Ferreira et al 2008). In this work we achieved cell viabilities up to 90 % and cell recoveries near 50 %.…”
Section: Resultsmentioning
confidence: 52%
See 3 more Smart Citations
“…It was recently reported that electroporation of cells in a capillary system gave rise to an enhancement of transfection rate and cell viability when compared to the cuvette system (Kim et al 2008). In the conventional electroporation, using a cuvette, the reported cellular viabilities are generally below 70 % and most importantly the cell recoveries are rarely mentioned, with the exception of few studies with primary cells (Aluigi et al 2006;Ferreira et al 2008). In this work we achieved cell viabilities up to 90 % and cell recoveries near 50 %.…”
Section: Resultsmentioning
confidence: 52%
“…The number of pulses (1-3) did not greatly affect the number of GFP + cells contrarily to some reported studies, although using different cell lines and electroporation equipments (Lin et al 2009). It is well known that when cells are submitted to high electric pulses a major amount of DNA enter into the cells though concurrently an increase of cell death is observed (Ferreira et al 2008). Several studies, using different cells, have shown that a way to circumvent this fact is by decreasing electric pulse and increasing the duration of pulse (pulse width) or within low voltages use more than one pulse (Cemazar et al 2009).…”
Section: Resultsmentioning
confidence: 80%
See 2 more Smart Citations
“…Nucleofection has been used successfully for transient transfection of human, bovine, rat and porcine MSCs, but has never been tested in BM-derived mMSCs. [34][35][36][37] Magnetically enhanced nucleic acid delivery (magnetofection) has not explored for any type of MSCs to date. We found that nucleofection is a very efficient transfection technique for mMSCs with transfection rates of B60%.…”
Section: Nonviral Gene Transfer Into Murine Mscsmentioning
confidence: 99%